2008
DOI: 10.1002/9780471729259.mc03c01s10
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Maintenance of Bartonella quintana

Abstract: Trench fever is the common name for the acute febrile syndrome associated with a Bartonella quintana bacterial infection. The focus of this unit is to describe reliable methods for cultivation and cryopreservation of B. quintana and can be applied to cultivation and preservation of all Bartonella. Detailed recipes for preparation of three types of semisolid media are also included.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…B. quintana was the only strain for which the presence of mammalian cells in the culture (M10-V medium) was a significant benefit to growth compared to the growth achieved by culture under the same conditions but with cell-free (M10) medium. These results agree with those from previous work suggesting that under mammalian cell culture-based conditions, cell coculture is important for B. quintana growth (3,22). Recent developments, however, have shown that cell culture is unnecessary when insect cell culture-based medium is used (28,32).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…B. quintana was the only strain for which the presence of mammalian cells in the culture (M10-V medium) was a significant benefit to growth compared to the growth achieved by culture under the same conditions but with cell-free (M10) medium. These results agree with those from previous work suggesting that under mammalian cell culture-based conditions, cell coculture is important for B. quintana growth (3,22). Recent developments, however, have shown that cell culture is unnecessary when insect cell culture-based medium is used (28,32).…”
Section: Discussionsupporting
confidence: 92%
“…The data were analyzed for each strain and between conditions at the time course endpoint of 9 days or at the peak of growth using the Kruskal-Wallis or Wilcoxon rank sum tests with 2 approximations. The day 9 endpoint was used for the purpose of comparing media and cell presence, as this was most biologically relevant to Bartonella culturing protocols, which usually require incubation for from 7 to 28 days (3,22,24). The peak growth of each strain was compared between temperatures at day 9, as it was the most logical point to show temperature-dependent differences because of such a discrepancy in growth at day 9, when the growth either plateaued or dramatically declined.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Bartonella bacilliformis was cultivated as previously described for B . quintana except the incubation temperature was 30°C and 5% CO 2 was omitted [ 13 ]. Briefly, h eart i nfusion b roth + sheep b lood (HIB-B) plates consisted of heart infusion broth containing 4% sheep blood, 2% sheep serum and 1.5% agar.…”
Section: Methodsmentioning
confidence: 99%